2015
DOI: 10.5455/2394-6040.ijcmph20150509
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs and practices regarding nutrition during pregnancy and lactation in a rural area in Karnataka, India: a qualitative study

Abstract: INTRODUCTIONNutrition plays a quintessential role with regard to maternal and child health. However, this aspect is inevitably interlinked to perceived notions and beliefs with regard to food to be consumed by pregnant and lactating women. Studies have also shown existence of practices and beliefs like denying pregnant and lactating women of known nutritious food items owing to their traditional food habits. [1][2][3] In India most food practices and traditions have stemmed from deeply rooted traditions and cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 6 publications
3
22
0
1
Order By: Relevance
“…While the reasons for the identified food taboos are not scientifically supported, they seem to have developed from the intention to prevent pregnancy complications for the mother and any health problem for the baby ( Table 2 ). These results were consistent with similar earlier studies done in other regions of Ethiopia and India [ 36 , 54 ]. There is also a fasting season for pregnant women who follow the Orthodox religion, requiring that they do not eat animal foods during the fasting period (which spans more than 180 days per year).…”
Section: Discussionsupporting
confidence: 94%
“…While the reasons for the identified food taboos are not scientifically supported, they seem to have developed from the intention to prevent pregnancy complications for the mother and any health problem for the baby ( Table 2 ). These results were consistent with similar earlier studies done in other regions of Ethiopia and India [ 36 , 54 ]. There is also a fasting season for pregnant women who follow the Orthodox religion, requiring that they do not eat animal foods during the fasting period (which spans more than 180 days per year).…”
Section: Discussionsupporting
confidence: 94%
“…Notably, a low-mixed vegetarian diet without fruits and pulses was the predominant pattern among women. Predominantly, vegetables and cereal-based diets among pregnant women in rural areas have been reported in other studies from India (27)(28)(29)(30). Green leafy vegetables are a good source of iron but have low bioavailability compared to animal sources.…”
Section: Discussionmentioning
confidence: 74%
“…In a study done by Puri and Kapoor, it is reported “one of the strong beliefs is that papaya can cause abortion.”[10] A study among 1,200 women from all districts of Tamil Nadu in India showed that 82% of women avoided papaya during pregnancy. [12] Saffron was believed to be responsible for fairer skin of the baby by the participants of few studies. [912] But, on the contrary, in this study, respondents were forbidden to eat any dark colored vegetables to prevent dark complexion of baby.…”
Section: Discussionmentioning
confidence: 99%